The end of the experiment? : from competition to the foundational economy /: from competition to the foundational economy. (2014) - Bowman, Andrew; Williams, Karel; Moran, Michael, 1946-; Leaver, Adam; Law, John, 1946-; Johal, Sukhdev; Froud, Julie; Ertürk, Ismail
No abstract available